RAILWAY DEVELOPMENT AND AIR PATRONAGE IN CHINA, 1993–2012: IMPLICATIONS FOR LOW‐CARBON TRANSPORT. (16th May 2016) - Li, Linna; Loo, Becky P.Y.
ABSTRACT: This study examines the interrelationship between railway development and air patronage in China from 1993 to 2012 by type of railway development and city pair distance. Two types of railway development are considered: railway extension and an increase in railway speed. Results of the panel data regression analysis show that railway development is associated with a reduction on air transport. However, the association between railway extension and air patronage is only significant for short‐ and medium‐haul city pairs but not for long‐haul ones, whereas the association between railway acceleration and air patronage is only significant for short‐haul city pairs. Nevertheless, the potential effect of railway development on the reduction of carbon emissions in China through a modal shift is relatively sizeable, with an approximately 6.9 percent net reduction (2.83 million tons) of the total carbon emissions from air and rail transport in 2010.